Desenvolvimento sustentável na Amazônia : um estudo do padrão espacial do desmatamento e do programa bolsa floresta - Almeida, Neuler André Soares de (2012)
The first article in this Dissertation demand their inclusion in the debates and discussions that address issues such as environmental policy, sustainable development, territorial development and forest legislation, within the context of the development of the state of Amazonas, in particular, a sustainable development program in execution in the state, called Bolsa Floresta (PBF). Although he started a few years ago, your profile (payment for environmental services) and its territorial approach seem to give him a character in the novel that deals with environmental policy in the region. Even very foolishly, he has been successful in solving problems as the service traditional populations, resolution of territorial conflicts and income generation. Regarding the second article deals with the same controversies existing between economic growth, sustainable development and environmental protection, raised from work as Grossman and Krueger (1995) that describe a relationship between GDP per capita and environmental degradation. Thus this paper aims to investigate this relationship through the identification of spatial patterns of variable deforestation in Amazonas and thus more specifically investigate the influence of income on deforestation, from two main interests (1) test the existence of the Environmental Kuznets curve, (2) measure the importance of the Bolsa Floresta program. For this, an econometric model was constructed with data Cross section for the year 2009, an estimation of Environmental Kuznets Curve for 62 municipalities in the state of Amazonas. The results point to the existence of an environmental CKA at Amazon with the presence of two spatial clusters.